Influence of particle size distribution on biocarbonation method produced microbial restoration mortar for conservation of sandstone cultural relics - Yang Yang; Shaokang Han; Hanlong Liu; Huili Chen; Siwei Jiang (Biogeotechnics)
Biocarbonation of reactive magnesia based on microbially induced carbonate precipitation (MICP) process is a sustainable geotechnical reinforcement technology for strength development and permeability reduction. This method can be used to produce microbial restoration mortar (MRM) for the application of stone cultural relics restoration. In this paper, the influence of particle size distribution on the strength and porosity of MRM was examined. By mixing fine and coarse sandstone powder in various proportions, nine different particle size distributions were obtained to investigate the restoration performance, including the unconfined compressive strength (UCS), porosity, and color difference. The results indicate that the well-graded particle size distribution can lead to the UCS improvement and porosity reduction of MRM. The findings also imply that adding fine sandstone powder to the coarse sandstone powder can provide extra bridging contacts within the soil matrix. These bridging contacts can be easily connected by the precipitated hydrated magnesium carbonates (HMCs) minerals, consequently resulting in more effective bonding and filling within the pore matrix. The microstructural images of MRM confirm the formation of HMCs, which exhibited a dense network structure, filling out the gap and bonding the sandstone powders. Furthermore, the microbial restoration mortar showed a high weather resistance to dry-wet cycles, acid rain, and salt attack, which is attributed to better stability and strength of HMCs than the original calcic cemented minerals in sandstone.